2009
DOI: 10.3844/ajessp.2009.664.668
|View full text |Cite
|
Sign up to set email alerts
|

Production of Potassium and Calcium Hydroxide, Compost and Humic Acid from Sago (Metroxylon sagu) Waste

Abstract: Problem statement: Agriculture waste such as Sago Waste (SW) has a potential to cause pollution when the waste is discarded into rivers. In order to add value to SW, a study was conducted to produce potassium and calcium hydroxide, compost and Humic Acid (HA) from SW. Approach: The SW was air-dried and some grinded. The grinded SW was incinerated at 600°C. Potassium and calcium hydroxide was extracted by dissolving the ash in distilled water at a ratio of 1:500 (ash: water), equilibrated for 24 h at 150 rpm us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A low C/N ratio gives higher results of fruiting bodies and supports better mushroom yield (Royse, 2002). Fresh sago waste contained the C/N ratio of 790.1 (Auldry et al, 2009) while SD contained the C/N ratio of 325.0 (Osunde et al, 2019). The fastest first harvest collected for P. sajor-caju (50.33 days) was recorded from the substrate formula of 100SD and significantly quicker than other substrate formulas, whereas the longest period taken for the first harvest collected (71.86 days) was obtained from the substrate formula of 100SB.…”
Section: Effects Of Various Substrate Formulas On Grey Oyster Mushroom Morphological Parametersmentioning
confidence: 99%
“…A low C/N ratio gives higher results of fruiting bodies and supports better mushroom yield (Royse, 2002). Fresh sago waste contained the C/N ratio of 790.1 (Auldry et al, 2009) while SD contained the C/N ratio of 325.0 (Osunde et al, 2019). The fastest first harvest collected for P. sajor-caju (50.33 days) was recorded from the substrate formula of 100SD and significantly quicker than other substrate formulas, whereas the longest period taken for the first harvest collected (71.86 days) was obtained from the substrate formula of 100SB.…”
Section: Effects Of Various Substrate Formulas On Grey Oyster Mushroom Morphological Parametersmentioning
confidence: 99%
“…Differences in the compost piles were also statistically significant (p < 0.05). Auldry et al (2009) identified an increase in ash content and humic acid due to a decrease in organic matter content over the composting period caused by mineralization and humification.…”
Section: Organic Matter Carbon Ash Content and C/n Ratiomentioning
confidence: 99%
“…However, an increase was realized later, which could be attributed to a decrease in compost mass due to degradation of organic carbon. Ajay and Kazmi (2007) and Auldry et al (2009), measured increase in total nitrogen during the composting process and attributed it to the decrease in substrate carbon resulting from the loss of CO 2 (due to the decomposition of the organic matter which is chemically bound with nitrogen).…”
Section: Macro-nutrientsmentioning
confidence: 99%